Enhancing the energy utilization in parabolic trough concentrators with cracked heat collection elements using a cost-effective rotation mechanism. (January 2022) - Amein, Hamza; Akoush, Bassem M.; El-Bakry, M. Medhat; Abubakr, Mohamed; Hassan, Muhammed A.
Abstract: The risk of vacuum loss in linear solar heat collection elements (HCEs) is one of the major practical challenges that are facing the parabolic trough solar concentrator (PTSC) systems in concentrating solar power (CSP) plants. Despite the long-life span of CSP systems, HCEs are frequently replaced due to permeated hydrogen (due to saturation of getters) or leaked air (due to failures in end metal-to-glass welding or cracked glass shells). This study proposes a low-tech solution for boosting the performance of PTSCs with partial or lost vacuum through rotating the HCEs. A carefully validated integrated 3D optical-thermal model is developed and used to quantify the energetic and exergetic performances of PTSCs with rotated and fixed HCEs for both cases of lost and maintained vacuum. Both steady and unsteady simulations are reported using high-precision ground measurements of direct irradiance and meteorological parameters. As the rotational speed increases from 0 to 20 rad/s, the energy efficiency of PTSCs with new and damaged HCEs is improved by ∼47 and 52%, respectively, at a Reynolds number of 4000 and an inlet temperature of 350 °C. By rotating a damaged HCE at only 10 rad/s, maximum improvements of ∼26 and 53% in the useful heat gain are obtained, compared to non-rotating evacuated and non-rotating damaged HCEs, respectively, at the same operating conditions. Overall, the advantage of the proposed concept is more pronounced when the PTSC is operating at relatively low flow rates, high temperatures, or under high irradiance levels. Graphical abstract: Image 1